Water stress thresholds for walnuts: Stem water potential baselines to maximize yield and water productivity - Beyá-Marshall, Victor; Lobos, G.; Calvo, Franco Emmanuel; Otárola, Jaime; Trentacoste, Eduardo Rafael (Elsevier, 2025)
Walnut (Juglans regia) cultivation in the Americas faces increasing challenges due to water scarcity and high irrigation demands. This study refines irrigation management strategies by establishing midday stem water potential (Ψₓ) baselines as a function of vapor pressure deficit (VPD): (i) a fully irrigated baseline, where the entire soil moisture is maintained near field capacity; and (ii) a non-stressed baseline, where Ψₓ reflects water content conditions that do not limit fruit size and yield. Additionally, detrimental Ψₓ thresholds are identified to optimize water productivity, nut yield, and quality. Multi-year, multi-location trials were conducted in ‘Chandler’ and ‘Serr’ orchards under diverse environmental and irrigation conditions. Results confirm that Ψₓ is strongly correlated with VPD, making it a reliable indicator of plant water status. Fully irrigated walnut trees maintain a Ψₓ between −0.3 and −0.5 MPa, while the non-stressed baseline ranges from −0.3 to −0.7 MPa in ‘Chandler’ and from −0.3 to −0.8 MPa in ‘Serr’ under wet and non-stressed soil conditions within a VPD range of 0.5–4 kPa. Validating the non-stressed Ψₓ baseline through production data demonstrated that optimizing irrigation based on this baseline improves water productivity by 20–25 % compared to fully irrigated treatments. Additionally, deficit Ψₓ thresholds (Ψₓ values below the full irrigation baseline) were established, defining the optimal range of water stress that balances yield, fruit size, and water savings. In ‘Serr’ maximum yield and fruit size were achieved when the Ψₓ deficit ranged from −0.15 to −0.40 MPa, peaking at −0.29 MPa. In contrast, ‘Chandler’ performed optimally within a narrower Ψₓ deficit range of −0.10 to −0.30 MPa, with a peak at −0.22 MPa. Beyond this threshold, yield losses increased progressively, reaching 25 % or more at higher water deficits. Furthermore, detrimental Ψₓ thresholds associated with 5–25 % yield losses were identified, providing critical decision-making tools for growers facing water scarcity. These findings emphasize the importance of Ψₓ monitoring in irrigation scheduling to enhance water efficiency, maintain high walnut productivity, and support sustainable orchard management in water-limited regions.